Long Term Effect of Acute Intestinal Obstruction Management following Laparotomy in a Tertiary Care Hospital (Journal of Current and Advance Medical Research, 2020)
Background: Post-surgical outcomes are very crucial for acute intestinal obstruction following laparotomy.Objective: The purpose of the present study was to identify the causes and risk factors that influence the outcome of post laparotomy acute intestinal obstruction and also to assess their management and outcome.Methodology: This cross sectional study comprising fifty patients irrespective of age and sex with diagnosis of Acute intestinal obstruction following laparotomy who attended at the Department of Surgery in different tertiary Hospital of Dhaka city, within the time period of July 2017 to June 2019. All these data were analyzed and tried to find out the outcome of management of acute intestinal obstruction following laparotomy.Results: All the 50 patients had undergone some conventional surgeries in previous instance. Acute intestinal obstruction was found in 80.0% of cases who had undergone emergency surgery and 20.0% cases were after routine surgery. The reasons behind Laparotomy for burst appendix (16.0%) followed by laparotomy for blunt trauma abdomen (12.0%) and classical appendicectomy (12.0%). After conservative management complication rate was low (21.0%) and the most prominent complication was UTI (28.57%) whereas mortality was 14.29%. After surgical management complication rate was higher which was in 56.25% of cases.Conclusion: Post laparotomy of acute intestinal obstruction can improve the outcome and reduce the chance of relaparotomy, surgical morbidity.Journal of Current and Advance Medical Research 2020;7(2): 73-79